Informed Health Choices media intervention for improving people’s ability to critically appraise the trustworthiness of claims about treatment effects: a mixed-methods process evaluation of a randomised trial in Uganda - Semakula, Daniel; Nsangi, Allen; Rosenbaum, Sarah; Fretheim, Atle; Sewankambo, Nelson (BMJ open, 2019)
We developed the informed health choices (IHC) primary school resources to teach children how to assess the trustworthiness of claims about the effects of treatments. We evaluated these resources in a randomised trial in Uganda. This paper describes the process evaluation that we conducted alongside this trial. To identify factors affecting the implementation, impact and scaling up of the intervention; and potential adverse and beneficial effects of the intervention.